Continued expansion of the Heart Team concept. (March 2015) - Passeri, Jonathan J; Melnitchouk, Serguei; Palacios, Igor F; Sundt, Thoralf M
ABSTRACT : The concept of a multidisciplinary Heart Team approach to treating cardiovascular disease has garnered increasing interest in recent years. This team-based approach has been a cornerstone of practice in other medical fields, such as oncology and solid organ transplantation. Advances in technology and new therapeutic strategies now offer multiple treatment options to patients with complex coronary artery or valvular heart disease, making therapeutic decision-making more challenging. There is a growing literature that use of a Heart Team for management of these complex cardiovascular diseases has demonstrated great merit. While the composition and implementation of Heart Team will vary, this multidisciplinary team-based approach will become the standard of care in cardiovascular medicine in the future.